Visual analysis of lung neuroendocrine tumors based on CiteSpace knowledge graph - Guo, Mingjie; Hu, Shaowen; Xiao, Yaifei; Cao, Zhan; Huang, Zhichao; Liu, Yalong; An, Xiaokang; Zhang, Guoyu; Zheng, Xianjie (Frontiers in Endocrinology, 2023)
Objective The relevant literatures in the field of pulmonary neuroendocrine tumor were analyzed to understand the lineage, hot spots and development trends of research in this tumor. Method The Web of Science core collection was searched for English-language literature about neuroendocrine tumors of the lung published between 2000 and 2022. CiteSpace software was imported for visualization analysis of countries, institutions, co-cited authors and co-cited journals and sorting of high-frequency keywords, as well as co-cited references and keyword co-occurrence, clustering and bursting display. Results A total of 594 publications on neuroendocrine tumours of the lung were available, from 2000 to 2022, with an overall upward trend of annual publications in the literature. Authors or institutions from the United States, Italy, Japan and China were more active in this field, but there was little cooperation among the major countries. Co-cited references and keyword co-occurrence and cluster analysis showed that research on diagnostic instruments, pathogenesis, ectopic ACTH signs, staging and prognosis and treatment was a current research hotspot. The keyword bursts suggested that therapeutic approaches might be a key focus of future research into the field for pulmonary neuroendocrine tumors. Conclusion Over these 20 years, research related to neuroendocrine tumors of the lung has increased in fervour, with research on diagnostic instruments, pathogenesis, ectopic ACTH signs, staging and prognosis, and treatment being the main focus of research. Therapeutic treatments may be the future research trend in this field.